Incidencia de las actitudes de padres de familia y maestra en la timidez de los niños y niñas del primer año de educación básica de la Escuela Fiscal Mixta “Eloy Alfaro” de la ciudad de Alamor, cantón Puyango, periodo lectivo 2010 – 2011. Lineamientos alternativos - Díaz Eras, Rosario Maribel (2011)
The present research work whose theme is: incidence of LAS attitudes of parents of family and teacher in the shyness of the boys and girls of the first year of education basic of the school Attorney joint ELOY ALFARO of the city of ALAMOR, Canton PUYANGO, LECTIVO period 2010-2011. ALTERNATIVE GUIDELINES. He served with the overall objective is to analyse the incidence of the attitudes of parents and teacher at the timidity of first year of basic education of the researched school children. As well as the specific objectives are: to determine the type of fathers and mothers responsible for this problem, describing the behavior of shy children of first year of education basic of the school Attorney joint Eloy Alfaro of the city of Puyango Canton Alamor. According to these objectives were two hypotheses were tested with the use of descriptive statistics, analysis and synthesis, as well as the implementation of the interview with the teacher, specs 26 learners observation and survey 26 parents of the researched institution, the results were analyzed and processed in a qualitative manner, demonstrating that the negative attitudes of the parents and the teacher really affect the timidity of the children and girls, since there is no good family relationships is to say children are developing in an atmosphere of insecurity, conflict, lack of emotional manifestations involving to be causal shy behavior of the child; It was detected within the main problems that exist in the classroom and at home is the shyness followed by little socialization in the environment. For this we recommend should be Act the child with freedom from run, jump, play, browse and investigate their surroundings, and these activities in the way you want, giving tasks that are easy to be taking security in itself. We also recommend to parents and mothers leave their children to places that serve as rest, relaxation, calm, game, sporting, cultural, artistic, activities with the aim of improving relations between them, achieving a change in attitudes that lead to a better coexistence, trust, love and understanding. These results were formulated the alternative that it will encourage families and master guidelines of the children of the aforementioned establishment and allow you to show an attitude suitable in the development of children, overcoming fear and shyness that prevent social integration with their peers; those which are reflected in the corresponding section.